Fresh and Hardened Properties of Different Percentages of Hybrid Kenaf-Glass Fibres Reinforced Geopolymer Concrete under Ambient Curing Condition - Maryam Firas, Al-Baldawi; Farah Nora Aznieta, Abdul Aziz; Norsuzailina, Mohamed Sutan; Noor Azline, Mohd Nasir; Khalina, Abdan; Al Ghazali, Noor Abbas; Muhammad, Zahid (Semarak Ilmu Publishing, 2025)
Geopolymer concrete (GPC) has become one of the alternative green materials to normal concrete due to its inherent advantages in minimizing carbon emissions for a sustainable environment. However, geopolymers have a brittle nature, hence integration of hybrid fibres in geopolymer concrete enhances its strength and ductility, mitigating fracture propagation. In this research, two types of fibres namely kenaf (KF) and glass fibres (GF) are hybrid to 1% of the total volume fraction added in fly Ash and GGBFS-based geopolymer concrete known as hybrid fibre-reinforced geopolymer concrete (HFGPC) with different percentages to identify the optimal percentage of the fibre mixture. The composite fresh and hard properties are determined from eight mixes to determine the workability, density, compressive strength and crack patterns. ANOVA was used to analyse the compressive strength results, indicating statistically significant enhancements in performance. The experimental results showed that the optimum HFGPC is 0.3KF-0.7GF mix achieved higher compressive strength characteristics around 51.2 MPa by 27% and 10.8% improvement compared with single KFs or GFs inclusion respectively. Moreover, increasing density and reducing crack propagation have been observed for the optimum hybrid mixture. This work provides insight into the performance of HFGPC, Promoting the utilization of sustainable construction materials in practical engineering.